The Textbook: The Teachers of Today - Céspedes, José Pablo (2011)
This is a research synthesis done with the goal of comprehending and interpreting the real role of textbooks in the classrooms. This paper shows the unnecessary usage of textbooks for conducting the teaching-learning process. Thestudy results were obtained at a private high school in Limon province which holds a medium-class population. Nonetheless, this institution possesses anexcellent infrastructure and parents pay a high fare, the educational quality resembles a public school one. This is due to the lack of correspondence between the curricular content and the teaching objectives that are established for this type of centers.